Diffusive gradients in thin-films (DGT) for in situ sampling of selected endocrine disrupting chemicals (EDCs) in waters. (15th June 2018) - Chen, Wei; Pan, Suhong; Cheng, Hao; Sweetman, Andrew J.; Zhang, Hao; Jones, Kevin C.
Abstract: A passive water sampler based on the diffusive gradients in thin-films (DGT) technique was developed and tested for 3 groups of endocrine disrupting chemicals (EDCs, including oestrogens, alkyl-phenols and bisphenols). Three different resins (hydrophilic-lipophilic-balanced (HLB), XAD18 and Strata-XL-A (SXLA)) were investigated for their suitability as the binding phase for DGT devices. Laboratory tests across a range of pH (3.5–9.5), ionic strength (0.001–0.5 M) and dissolved organic matter concentration (0–20 mg L −1 ) showed HLB and XAD18-DGT devices were more stable compared to SXLA-DGT. HLB-DGT and XAD18-DGT accumulated test chemicals with time consistent with theoretical predictions, while SXLA-DGT accumulated reduced amounts of chemical. DGT performance was also compared in field deployments up to 28 days, alongside conventional active sampling at a wastewater treatment plant. Uptake was linear to the samplers over 18 days, and then began to plateau/decline, indicating the maximum deployment time in those conditions. Concentrations provided by the DGT samplers compared well with those provided by auto-samplers. DGT integrated concentrations over the deployment period in a way that grab-sampling cannot. The advantages of the DGT sampler over active sampling include: low cost, ease of simultaneous multi-site deployment, in situ analyte pre-concentration and reduction of matrix interferences compared with conventional methods. Compared to other passive sampler designs, DGT uptake is independent of flow rate and therefore allows direct derivation of field concentrations from measured compound diffusion coefficients. This passive DGT sampler therefore constitutes a viable and attractive alternative to conventional grab and active water sampling for routine monitoring of selected EDCs. Graphical abstract: Highlights: Diffusive gradients in thin films (DGT) was developed for endrocrine disrupting chemicals (EDCs). DGT performance with HLB and XAD18 resins is independent of a range of environmental conditions. DGT used to monitor EDCs in wastewaters compares favourably with conventional sampling. DGT is quantitative, efficient, robust and cost-effective for environmental monitoring of EDCs.